Participatory Design Process in Post-Disaster Housing Production: the Case of October 30, 2020 İzmir Earthquake - Yılmaz, Ebru; Çelik, Saniye Dilara (01. Izmir Institute of Technology, 2022)
A housing problem after a disaster is a problem that can occur suddenly. This thesis will emphasize why participatory design should be preferred, especially post-disaster housing production. Due to the nature of participation, the community can overcome post-disaster traumas in a more comfortable and controlled manner. Society needs to come out of the post-disaster situation with solidarity and unity. Participation can be achieved through solidarity, communication, cooperation, trust, and a sense of belonging. On the other hand, participatory design answers this urgent problem after the disaster. The thesis aims to examine the concept of participatory design around four main components: actor, process, method, and end product. The first part gives the literature’s theoretical explanations and history of participation and participatory design concepts. The second part discussed the post-disaster housing problem, and examples of post-disaster housing projects produced with a participatory design focus were examined. These examples were compared based on the four components of participation. Then, the struggle plan, which was carried out after the devastating October 30 Izmir Earthquake we experienced last year, was examined. For this examination, firstly, information was collected, and then reality measurement was made with survey and interview methods. A study concluded by comparing the statistical data obtained from the questionnaire with the information collected.

Afet sonrası konut sorunu aniden gerçekleşebilecek bir problemdir. Bu tezde özellikle afet sonrası konut üretiminde katılımcı tasarımın neden tercih edilmesi gerektiği vurgulanacaktır. Katılımın doğası gereği afet sonrası travmalar daha rahat ve kontrollü biçimde atlatılabilir. Toplumun afet sonrası içinde bulunduğu durumdan dayanışma ve birliktelik ile çıkması gerekir. Katılım dayanışma, iletişim, iş birliği, güven ve aidiyetlik duygusu ile gerçekleşebilir. Katılımcı tasarım ise afet sonrası oluşan bu acil probleme cevap niteliğindedir. Tez, katılımcı tasarım kavramını dört ana bileşen etrafında incelemeyi hedefler; bu bileşenler aktör, süreç, metot ve sonuç üründür. İlk bölümde katılım ve katılımcı tasarım kavramlarının literatürdeki teorik açıklamaları ve tarihçesi aktarılmıştır. İkinci bölümde ise afet sonrası konut sorunu ele alınmış ve katılımcı tasarım odaklı üretilen afet sonrası konut projesi örnekleri incelenmiştir. Bu örnekler birbirleri ile katılımın dört bileşeni baz alınarak karşılaştırılmıştır. Daha sonra ise geçen sene yaşadığımız yıkıcı 30 Ekim İzmir Depremi sonrasında yürütülen mücadele planı incelenmiştir. Bu inceleme için önce bilgi toplanmış daha sonra ise anket ve röportaj yöntemleri ile gerçeklik ölçümü yapılmıştır. Anketten çıkan istatistik veri ile toplanan bilgiler karşılaştırılarak sonuca varılmıştır.
Afet Sonrası Konut Üretiminde Katılımcı Tasarım Süreci: 30 Ekim 2020 İzmir Depremi Örneği
Thesis (Master)--Izmir Institute of Technology, Architecture, Izmir, 2022
Includes bibliographical references (leaves. 102-112)
Text in English; Abstract: Turkish and English
Keywords: Disaster housing; Disaster management; Participatory design; İzmir Earthquake